(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article focuses on the first theatrical production of The Serpent, Nelson Rodrigues’ last play, performed in Rio de Janeiro in 1980, directed and set designed by Marcos Flaksman. Based on research into the productionand an interview with the director, historiographical data was compiled and the critical reception of the play, the playwright’s role in the production and the director’s scenic and aesthetic choices were analyzed, finally dealing with the process of creating spatiality for this scene.